Literature Study: Factors Affecting Prognostics of Head Injury Patients - Indri Wahyuningsih; Nur Islamiati; Zaqqi Ubaidillah; Indah Dwi Pratiwi (PT FORMOSA CENDEKIA GLOBAL, 2022)
Head injury is often referred to as “the silent epidemic” remains a public health problem and is the largest contributor to mortality and record among all injuries. The aim of this study was to identify the prognostic factors in head injury patients based on a literature study. The research design used in this study was a literature study with a sample of 15 journals, Google Scholar (n=3), Pubmed (n=4), proQuet(n=4), Science Direct (n=4). The results of this study are that there are factors that influence the prognostication of head injury patients including age (11 journals), GCS (Glasgow Coma Scale) (11 journals), gender (3 journals), and hematoma (4 journals). Prognostic factors of head injury were found in 15 journals, including age, GCS (Glasgow Coma Scale), gender, and hematoma.